Penggunaan Instagram @Infobnn_kota_Samarinda dalam Mensosialisasikan Program Pencegahan dan Pemberantasan Penyalahgunaan dan Peredaran Gelap Narkotika (P4GN) di Kota Samarinda - Herliani, Ade; Sucipta, Johantan Alfando Wikandana; Purwanti, Silviana; Hairunnisa (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
The research aims to describe how Instagram @infobnn_kota_samarinda is used in socializing the P4GN Program in Samarinda City using a research focus based on four criteria in the Media Wealth Theory by Daft and Lengel, namely: 1) Immediacy; 2) Cue Diversity; 3) Language Variations; and 4) Personal Sources. This research uses a qualitative descriptive research method by analyzing data in oral and written form, as well as in the form of images or photos, which are collected through observation, interviews and documentation, so that discoveries and in-depth understanding can be obtained to answer the research problem formulation. The results of this research are that the use of Instagram @infobnn_kota_samarinda has met the four criteria in Media Richness Theory, namely that Instagram social media can provide immediate feedback, provide a variety of verbal and non-verbal signals, language variations to increase audience understanding, and convey messages that can meet information needs and is able to influence the feelings and emotions of the audience. However, there were findings on the Immediacy criteria that there was a delay in Promptly providing the latest information and minimal interaction was provided because Instagram @infobnn_kota_samarinda was less active in replying to Instagram users' comments.